OPTIMALISASI PEMASOK DAN PERENCANAAN BAHAN BAKU YANG OPTIMAL PADA SUBANDI COLLECTION - Muhammad Mutamal Liqin Wahab; Endang Widuri Asih; Petrus Wisnubroto (Jurnal Rekavasi, 2016)
Subandi Collection is a home industry that produces leather sandals. An increase in product sales process, Subandi Collection must have a plan of raw materials optimized by adjusting the lavel of sales, so do not store raw materials exaggerated in the warehouse resulting in storage costs over, so there is no shortage of raw maetrials in the supply of raw materials which will be in production. In the event of a shortage of raw materials would disrupt the production process and cause harm to Subandi Collection. In the absence of optimal supplier selection in the planning of raw materials have resulted in a build up of raw materials excessive costs on storage. The purpose of this study to determine the optimal supplier according the criteria of the home industry and raw material requirements planning. To solve the problems of the supplier selection method Analythic Hierarchy Process (AHP) and to solve the problems of ordering or planning the size of the raw material used methods Silver Meal (SM). From the research results supplier of Kalimantan is the optimal supplier with priority weight of 0,39. Safety stock must be owned spon 3 sheet, vinyl 0 m2, and skin 2 feet. Lot size entirely an order as many as 18 times with a reorder point spon 7 sheets, vinyl 8,05m2, and the skin of 6,14 feet. For reservation for the lot size of order spon 180,12 sheet, vinyl 241,54 m2, and skin 124,32 feet.